Teaching English Writing with Inductive Reasoning: Do EFL Students Need to be Assisted to Learn Inductively? - รุ่งวรพงศ์ ปิยวรรณ (วารสารศึกษาศาสตร์ มหาวิทยาลัยสงขลานครินทร์ วิทยาเขตปัตตานี, 2024)
The paper reports on an experiment that was conducted in an EFL context to assess a learning aid called “Induction Helper” in a business correspondence writing course. Two tests were devised to collect data: a writing knowledge test and a writing skill test. Participants were 52 third-year Business English majors. Results indicate a significant difference in the posttest writing-skill scores of the control group (M = 12.00, SD = 1.65) and the experiment group (M = 15.65, SD = 2.17); t (50) = 6.83, p < .01. This signifies that although inductive instructions helped EFL students improve their business writing, the students who used the Induction Helper were able to write significantly better than those who didn’t. There was not a significant difference in the mean scores of the writing-knowledge retention test of the experiment group (M = 16.50, SD = 2.30) and the control group (M = 15.08, SD = 3.20), t (50) = 1.84, p= .072. However, there was a significant difference in the mean scores of the skill retention test of the experiment group (M = 15.40, SD = 1.81) and the control group (M = 10.96, SD = 1.48), t (50) = 9.67, p < .01. These results suggest that the Induction Helper helps EFL students improve and retain both their knowledge and writing skill on a long-term basis at a statistically significant level. The study also found that that knowledge and skills are separate concepts and that the possession of knowledge doesn’t necessarily ensure the application of that knowledge in practice.